2019
DOI: 10.1108/jea-08-2017-0094
|View full text |Cite
|
Sign up to set email alerts
|

Leadership style, occupational perception and organizational citizenship behavior in the Arab education system in Israel

Abstract: Purpose The field of educational systems has witnessed an increase in studies of organizational citizenship behavior (OCB) as it contributes to the effectiveness and success of schools and achieving their objectives and goals. The purpose of this paper is to examine the relationships between principals’ leadership style, occupational perceptions and OCB. Design/methodology/approach The research hypothesis holds that the leadership style (transformational or transactional) have a direct and indirect effect on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
27
0
6

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(36 citation statements)
references
References 57 publications
(69 reference statements)
3
27
0
6
Order By: Relevance
“…First, the current findings contribute to the OCB literature with respect to its relationship with levels of differentiation and integration ability. Recent research on OCB has emphasized leadership style, such as transformational (Arar & Abu Nasra, 2019), charismatic (Babcock-Roberson & Strickland, 2010), or ethical (Li et al, 2010). This research adds another cognitive trait to the examination of OCB by taking into consideration levels of CC in their effect on OCB.…”
Section: Discussionmentioning
confidence: 99%
“…First, the current findings contribute to the OCB literature with respect to its relationship with levels of differentiation and integration ability. Recent research on OCB has emphasized leadership style, such as transformational (Arar & Abu Nasra, 2019), charismatic (Babcock-Roberson & Strickland, 2010), or ethical (Li et al, 2010). This research adds another cognitive trait to the examination of OCB by taking into consideration levels of CC in their effect on OCB.…”
Section: Discussionmentioning
confidence: 99%
“…Figura 6. Liderazgo directivo como potenciador de la resiliencia educativa Es así como el líder directivo resiliente utiliza la creación de confianza del capital social como instrumento de mediación para la ejecución del proyecto educativo a través de la capacidad de generar motivación y compromiso por parte del plantel docente y el alumnado (Arar y Abu Nasra, 2019;Li et al, 2016).…”
Section: Liderazgo Directivo Desde La Resilienciaunclassified
“…En el sector de la Educación, la selección de directivos en Chile depende del sistema de Alta Dirección Pública (ADP), cuyo objetivo es dotar profesionales con las competencias necesarias para la dirección de establecimientos educacionales con dependencia estatal (Agencia de Calidad de la Educación [ACE], 2017), estableciendo en su mandato institucional la búsqueda de directivos con capacidades (individuales) de liderazgo, relacionadas al ejercicio administrativo y no enfocadas en la capacidad de motivación y en el desarrollo de un alto nivel de compromiso con el proyecto educativo, sin usar el ejercicio de prácticas coercitivas (Arar y Abu Nasra, 2019).…”
Section: Introductionunclassified
“…Investigations of the leadership issues in the education field have found strategies for better human resources management and improving employee performance. Some related research has shown an increasing interest in the effect of transformational leadership (TFL) and/or transactional leadership (TAL) of management on the outcomes and efficiency of staff in schools environments (Abu Ali et al, 2014;Arar and Abu Nasra, 2019;Massoudi, 2020;Nahum-Shani and Somech, 2011;Raewf and Thabit, 2015). Leaders following TFLs would inspire the confidence, loyalty, and respect of dependents and motivate them to participate in organizationfriendly conduct that exceeds expectations (Bass, 1985); in contrast, TAL leaders are subject to pre-determined targets based on rewards and contingent incentive strategies and outstanding management (Bass and Avolio, 1990;.…”
Section: Introductionmentioning
confidence: 99%